Molecular Weapons Contribute to Intracellular Rhizobia Accommodation Within Legume Host Cell - Syska, Camille; Brouquisse, Renaud; Alloing, Geneviève; Pauly, Nicolas; Frendo, Pierre; Bosseno, Marc; Dupont, Laurence; Boscari, Alexandre (Frontiers in Plant Science, 2019)
The interaction between legumes and bacteria of rhizobia type results in a beneficial symbiotic relationship characterized by the formation of new root organs, called nodules. Within these nodules the bacteria, released in plant cells, differentiate into bacteroids and fix atmospheric nitrogen through the nitrogenase activity. This mutualistic interaction has evolved sophisticated signaling networks to allow rhizobia entry, colonization, bacteroid differentiation and persistence in nodules. Nodule cysteine rich (NCR) peptides, reactive oxygen species (ROS), reactive nitrogen species (RNS), and toxin–antitoxin (TA) modules produced by the host plants or bacterial microsymbionts have a major role in the control of the symbiotic interaction. These molecules described as weapons in pathogenic interactions have evolved to participate to the intracellular bacteroid accommodation by escaping control of plant innate immunity and adapt the functioning of the nitrogen-fixation to environmental signalling cues.